(untitled) (Journal of the Bangladesh Agricultural University, 2026)
Morphological variation is a fundamental component of taxonomic research and provides critical insights into population-level biological and ecological differentiation. The present study investigated inter-population morphological variability in the freshwater mussel Lamellidens marginalis collected from three ecologically distinct freshwater habitats from North Central Bangladesh. Specimens (n = 100 per site) were sampled from Darikathal Beel, Trishal, Mymensingh (S1); the Old Brahmaputra River near the Botanical Garden, Bangladesh Agricultural University, Mymensingh (S2); and a pond adjacent to Boali Jam-E-Masjid, Tangail (S3) during December 2023. Twenty-three morphometric, mass-related, and derived ratio parameters were analyzed, including shell dimensions, soft tissue traits and proportional indices. Statistical comparisons revealed significant differences (p < 0.05) in 19 of the 23 parameters among at least two populations, indicating pronounced habitat-associated morphological divergence. Shell proportional indices demonstrated clear habitat-specific patterns. The SL/SH ratio indicated greater shell elongation in riverine population compared to the beel population. Conversely, ST/SH and SL/ST ratios suggested that pond-dwelling mussels possessed comparatively rounder and thinner shells than those from beel and riverine habitats. Condition index differed significantly (p < 0.05) between riverine and beel populations, reflecting a gradient of habitat suitability ranked as river > pond > beel. Overall, the findings highlight the strong influence of habitat-specific environmental conditions on shell morphology and physiological condition in L. marginalis. These results underscore the importance of integrating morphological assessments with molecular genetic analyses to achieve a more robust understanding of population structure and taxonomic resolution of L. marginalis across heterogeneous freshwater ecosystems in Bangladesh. J Bangladesh Agril Univ 24(2): 157–166, 2026